Leadership Post the Covid-19 Pandemic: Organization Perspective - Endah Suci Damayanti; Agus Dharmanto; Ardo Dwitanto; Tri Widyastuti; Bambang Karsono (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this scientific article is to provide an input on leadership after the covid 9 pandemic from the organizational side with material for comparing the results of related scientific articles, The research method used is qualitative using literature studies from existing scientific articles discussing leadership after covid 19, below will be displayed a metric table of scientific articles that make findings related to leadership as follows, The results of research on leadership results in the post-Covid 19 pandemic, various leadership styles that exist in organizations used such as transformational leadership, holistic leadership, leadership in the field of education, leadership in the field of hospitality, leadership in government organizations, post covid 19 pandemic leadership roles in each organization with the leadership abilities of each individual. Studies from several researchers (Fernandez & Shaw, 2020), (Zhao et al., 2020), (Glenn et al., 2020), (Dirani et al., 2020), (Anholon et al., 2020), (Craig & Amernic, 2020), (Wilson, 2020) are in accordance with the expectations of these researchers and scientific articles